Spin‐lock relaxation rate dispersion reveals spatiotemporal changes associated with tubulointerstitial fibrosis in murine kidney. Issue 4 (6th March 2020) - Wang, Feng; Colvin, Daniel C.; Wang, Suwan; Li, Hua; Zu, Zhongliang; Harris, Raymond C.; Zhang, Ming‐Zhi; Gore, John C.
Abstract : Purpose: To develop and evaluate a reliable non‐invasive means for assessing the severity and progression of fibrosis in kidneys. We used spin‐lock MR imaging with different locking fields to detect and characterize progressive renal fibrosis in an hHB‐EGF Tg/Tg mouse model. Methods: Male hHB‐EGF Tg/Tg mice, a well‐established model of progressive fibrosis, and age‐matched normal wild type (WT) mice, were imaged at 7T at ages 5–7, 11–13, and 30–40 weeks. Spin‐lock relaxation rates R 1 ρ were measured at different locking fields (frequencies) and the resultant dispersion curves were fit to a model of exchanging water pools. The obtained MRI parameters were evaluated as potential indicators of tubulointerstitial fibrosis in kidney. Histological examinations of renal fibrosis were also carried out post‐mortem after MRI. Results: Histology detected extensive fibrosis in the hHB‐EGF Tg/Tg mice, in which collagen deposition and reductions in capillary density were observed in the fibrotic regions of kidneys. R 2 and R 1 ρ values at different spin‐lock powers clearly dropped in the fibrotic region as fibrosis progressed. There was less variation in the asymptotic locking field relaxation rate R 1 ρ ∞ between the groups. The exchange parameter Sρ and the inflection frequency ω infl changed by larger factors. Conclusion: Both Sρ and ω infl depend primarily on the average exchange rate between water and other chemically shifted resonances such as hydroxyls and amides. Spin‐lock relaxation rate dispersion, rather than single measurements of relaxation rates, provides more comprehensive and specific information on spatiotemporal changes associated with tubulointerstitial fibrosis in murine kidney.